A importância da afetividade na educação para valores - Baltazar, Isabel (2020)
This report was carried out under the Curricular Practice Unit for Supervised Teaching of the Master Degree level for the Qualification for Teaching in Pre-School Education. This inquiry has as main objective to understand the paper of the affection on the education for values, having in consideration the pedagogical experience of the Educators of Infancy. The education for values must be day to day part of any educational establishment, and fits to the educator to motivate and to provide generating moments of the estimated values through this affective and pedagogical relation.The elaboration of activities of all the areas of knowing,or,simply, the planning of the routine activities are, moments of this affective experience, motivating source for the Education for Values. At established affective relations between educators and children are one more value for a good performance in any room of activities. To understand rhe perception of the educators of infancy face to this subject, it was necessary to inquire a set of educators. Thus our study it counts on a total of 125 inquired that they had answered to a questionnaire of open and closed answers previously construced for the effect. Afeter the retraction of the inquiries for questionnaire followed it interpretation of its data. We proceed to the analysis of the answers for the qualitative methodology although the used instrument to be an inquiry and to proceed to the numerical resource in percentile form to deal with some the questions. In the end we can conclude that the infancy educators promote the education for values as well as foment the relations affective. We can still affirm that it exists a relation between affectivity and education for values.